Geopolicy of the Black Sea region - Jeftić Nevenka (Međunarodni Problemi)
The author describes historical and contemporary geopolitical position of the Black Sea region. Up to the present times the primary significance of the region has lain in its trade routes and other transit communications that connect Europe, the Middle East and Asia. Having such geographic position the region has been an interest sphere of great powers and regional states and conquerors. Today most of states of the Black Sea region are economically poor, have unstable political systems and burdened with constant and potential explosive problems.